ANALYSIS OF METACOGNITIVE AWARENESS OF PROSPECTIVE BIOLOGY TEACHER STUDENTS THROUGH CREATIVE WRITING BULLET JOURNALING - Widya Arwita; Aswarina Nasution; Onggal Sihite (Universitas Negeri Medan, 2023)
Class of 2020 students face practical lectures such as Real Work Lectures and Introduction to the School Field as well as preparation for the final Thesis assignment. These lectures are not specifically scheduled in the study program, but are related to the partners where the students practice. This is a challenge for students in managing time and independence in carrying out academic activities. The ability to manage time, plan activities and carry out evaluations are metacognitive aspects needed by students. Therefore, this research aims to analyze students' metacognitive awareness through creative bullet journaling writing. The research population was all students of the Class of 2020 biology education at Medan State University who were taking KKN & PLP courses. The sample consisted of 30 students taken randomly. The data collection technique is carried out by providing bullet journaling before the new semester begins. Then students are given time to fill in the journal for approximately 3 months. Data analysis was carried out descriptively quantitatively. The research results show that students have classical metacognitive awareness in the well-developed category. Based on declarative, procedural and conditional aspects of knowledge; monitoring and evaluating are in the well developed category, while for the planning aspect the category is starting to develop. Based on these findings, it is necessary to train students to. Write a journal regularly so that metacognitive awareness can be further improved until the category develops very well